Alterità Esperienze e percorsi nell'Europa moderna - FELICI, LUCIA (Strumenti per la didattica e la ricerca, 2014)
The contributions collected in this volume are the result of the seminars organized by the Laboratory of Modern History during its ten-year activity (from 2003 to 2013) within the Department of Historical and Geographical Studies (now called SAGAS Department) of the University of Florence. Thanks to the participation of Italian and international colleagues, as well as young scholars, this annual cycle of seminars, entitled Temi e problemi della storia moderna ("Themes and problems of Modern History"), aims at encouraging the scientific community to discuss and reflect critically on topics of great historical importance. The theme of otherness is central in the Modern Age as well as in in the contemporary world, and it has been the subject of several seminars. The essays reconstruct significant moments and aspects of the relationships with "the other" in modern Europe: political models and cultural paradigms, cities of refuge and institutes of conversion, attitudes showing integration and/or exclusion of the Jews, Muslims, heretics and foreigners have been analysed in the volume according to the Laboratory's 'pluralistic spirit'.